Changes in predicted lean body mass, appendicular skeletal muscle mass, and body fat mass and cardiovascular disease. Issue 2 (25th February 2022) - Kim, Seong Rae; Lee, Gyeongsil; Choi, Seulggie; Oh, Yun Hwan; Son, Joung Sik; Park, Minseon; Park, Sang Min
Abstract: Background: Little is known about the association of changes in two body components, muscle and fat mass, with the risk of cardiovascular disease (CVD) among young adults. We investigated the association of changes in predicted lean body mass index (LBMI), appendicular skeletal muscle mass index (ASMI), and body fat mass index (BFMI) with the development of CVD among young adults. Methods: This nationwide, population‐based cohort study included 3 727 738 young adults [2 406 046 (64.5%) men and 1 321 692 (35.5%) women] aged 20–39 years without a previous history of CVD who underwent two health screening examinations during 2009–2010 and 2011–2012. Using validated and robust prediction equations, we calculated the changes in predicted LBMI, ASMI, and BFMI from the first to the second examinations. Results: The mean (SD) age was 32.2 (4.9) years, and 2 406 046 (64.5%) of the participants were men. A total of 23 344 CVD events were detected during 22 257 632 person‐years of follow‐up. Each 1 kg/m 2 increase in predicted LBMI and ASMI change was associated with a reduced risk of CVD among men [adjusted hazard ratio (aHR): 0.86, 95% confidence interval (CI) 0.82–0.91; aHR: 0.76, 95% CI 0.69–0.82, respectively] and women (aHR: 0.77, 95% CI 0.63–0.95; aHR: 0.75, 95% CI 0.59–0.96). Each 1 kg/m 2 increase in predicted BFMI change was associated with an increased risk of CVD among men (aHR: 1.16, 95% CI 1.10–1.22) and women (aHR: 1.32, 95% CI 1.06–1.65). In both sexes, decreases in predicted LBMI and ASMI were associated with greater CVD risk, and decreased predicted BFMI was associated with a reduced CVD risk. Those who maintained their BMI between −1 and +1 kg/m 2 also had a decreased risk of CVD per 1 kg/m 2 increase in predicted LBMI and ASMI change among men (aHR: 0.86, 95% CI 0.80–0.92; aHR: 0.85, 95% CI 0.76–0.95) and women (aHR: 0.62, 95% CI 0.47–0.83; aHR: 0.59, 95% CI 0.44–0.80) and had a greater risk of CVD per 1 kg/m 2 increase in predicted BFMI change among men (aHR: 1.17, 95% CI 1.10–1.25) and women (aHR: 1.64, 95% CI 1.20–2.23). Regardless of changes in weight, such as from normal to obese or vice versa, these results were consistent. Conclusions: Among young adults, increased predicted muscle mass or decreased predicted fat mass were associated with a reduced risk of development of CVD. Decreased predicted muscle mass or increased predicted fat mass were associated with an elevated risk of development of CVD.